A Latent Profile Analysis of drinking motives among heavy drinking college students. (December 2015) - Cadigan, Jennifer M.; Martens, Matthew P.; Herman, Keith C.
Abstract: Introduction: Positively (Enhancement and Social) and negatively (Coping) reinforcing drinking motives have been shown to be associated with alcohol use, alcohol-related problems, and depression among college students. Although prior studies of drinking motives have mostly consisted of variable-centered analyses, the current study used a person-centered approach where individuals were grouped into categories based on shared characteristics using Latent Profile Analysis (LPA). We investigated the utility of drinking motive profiles to determine how different profiles were associated with alcohol outcomes and depressive symptoms. Method: Participants were 648 undergraduate students who had violated a university alcohol policy and who endorsed consuming alcohol in the past month. Social, Coping, and Enhancement subscales from the Drinking Motives Questionnaire were used as indicators. Results: After examining one-through-eight class LPA solutions, the six-class solution provided the best empirical and clinically meaningful fit to the data. Classes with high coping and high positive reinforcing drinking motives consumed more alcohol than profiles of students with high coping and low positive reinforcing motives. Classes high on both coping and positively reinforcing motives reported the most alcohol related problems. Classes with higher levels of coping motives and either high or low positive reinforcing motives reported the highest depression symptoms. Conclusions: Drinking motive profiles differ in terms of alcohol outcomes and depressive symptoms. We encourage researchers to explore motives for drinking with individuals, especially assessing the relationship between coping motives and depression in the presence or absence of positively reinforcing motives. Highlights: Positively (PR) and negatively reinforcing (Coping) drinking motives were used. Six-classes best fit the data. Classes with higher PR motives drank more. Classes with high coping/high PR drank more than high coping/low PR classes. Classes with high coping/high PR had the most alcohol related problems. Classes with high coping, with either high or low PR, were the most depressed.